(untitled) (Journal of the Bangladesh Agricultural University, 2019)
A field experiment was carried out at the Horticulture Farm, Bangladesh Agricultural University, Mymensingh during the period from November 2011 to February 2012 to study the effect of seed tuber size on the yield and quality of seven accessions of potato. The experiment was laid out in the Randomized Complete Block Design (RCBD) with three replications. This piece of research consisted of two factors namely, size of seed tubers i.e. three different size of seed tuber i.e. small (10-20 g), medium (21-30 g) and large (31-40 g) and seven accessions of potato i.e. AC10064, AC10076, AC10097, AC10109, AC10123, AC10190 and one check variety Cardinal. The size of individual plot was 1.8 m × 1.2 m. Two adjacent unit plots and blocks were separated by 0.5 m and 0.5 m. A spacing of 60 cm × 30 cm was also used in terms of planting. Data on different yield contributing characters and yield were recorded. The tallest plants were produced by the large size of seed tuber accession AC10109 (120.25 cm) which also took minimum time (6.10 days) to germinate and possessed maximum stem diameter (0.95 cm) while small seed tuber of Cardinal required maximum days (10.23 days) along with shortest height (60.22 cm) as well as stem diameter (0.65 cm). The large size seed tuber of accession AC10109 gave maximum number of main stems/hill (6.4) and small size of seed tuber variety Cardinal gave minimum number of main stems/hill (2.96). The large size of seed tuber accession AC10109 produced maximum number of compound leaves/hill (64.80) and the small size of seed tuber Cardinal produced minimum number of compound leaves/hill (35.74). In terms of yield character large size of seed tuber of AC10109 accession exhibited highest results in tuber number 9.60 with the average diameter of tubers (5.86 cm) and yield was 10.42 t/ha. The accessions differed significantly with respect to all the plant characters studied. J. Bangladesh Agril. Univ. 17(2): 200–205, June 2019